1992
DOI: 10.1089/vim.1992.5.221
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Synthetic Peptides with Sequences of Rubella Virus E1 Polypeptide by Antibodies and T Lymphocytes

Abstract: Antigenicity of rubella virus E1 polypeptide was analyzed using synthetic peptides with predicted amino acid sequences. Overlapping solid-phase bound peptides were used to define antibody binding domains and a panel of free peptides to study T-cell responsiveness. Several antibody-binding areas including those earlier described to contain major neutralizing epitopes were recognized by human sera positive for rubella antibodies. T-cell lines specific for rubella virus were established from 14 rubella immune sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…We identified and further characterized three major T helper cell epitopes in RVE1 glycoprotein. Both fusion proteins and synthetic peptides have been applied to this kind of study [13][14][15][16]. Lovett and coworkers detected PBMC responses to a fusion protein covering aa 162-332 in 17 (41%) of 41 studied seropositive donors.…”
Section: Discussionmentioning
confidence: 99%
“…We identified and further characterized three major T helper cell epitopes in RVE1 glycoprotein. Both fusion proteins and synthetic peptides have been applied to this kind of study [13][14][15][16]. Lovett and coworkers detected PBMC responses to a fusion protein covering aa 162-332 in 17 (41%) of 41 studied seropositive donors.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (MAbs) were used to define the neutralizing domains on the E1 glycoprotein whose amino acid sequences were determined by overlapping synthetic peptides (9,11,12,14,21,22,24). One of these domains was defined by three independent MAbs that recognized the same sequence, represented by the synthetic peptide SP15 (E1 amino acids 208 to 239) (4, 25).…”
Section: Rubella Virus (Rv) Is the Etiologic Agent Of German Measlesmentioning
confidence: 99%
“…Both E1 and E2 provide life-long immunity, but the E1 glycoprotein is the major outward projecting structure and contains epitopes recognized by neutralizing and hemagglutinating inhibition antibodies, properties that make this protein a major candidate for a subunit or synthetic vaccine (5,6,(14)(15)(16). Many investigators have reported several sequences of amino acids of E1 with the ability to induce neutralizing antibodies (7,8,16). Overlapping synthetic peptides have permitted successful identification of neutralization domains.…”
mentioning
confidence: 99%